THE EFFECTIVENESS OF TIKTOK VIDEOS IN IMPROVING STUDENTS’ LISTENING COMPREHENSION AT SMP NEGERI 1 TONDANO - Mokoginta, Sustri; Rorimpandey, Rinny; Lolowang, Imelda S. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The Purpose of this research was to know whether using TikTok videos effective in improving students’ listening comprehension. The researcher conducted the study on the 9 grades of students of SMP Negeri 1 Tondano in the 2022/2023 academic year. The research design used was an experimental design with a quantitative approach, this pre-experimental research was conducted by using pre-test treatment, and post-test. The instrument used in this research was a test (pre-test and post-test). The population of this research is the students of eighth grade at SMP Negeri 1 Tondano which consists of two classes and the researcher took 21 students in each class to apply the test. The instrument in this research is a test. The kind test was used multiple choice test and the total number of multiple choices was 24 number. The test be based on the material given. Data was collected starting from making the lesson plan in the teaching and learning process, giving the pre-test, before presenting the material, analyzing the data taken from the pre-test and post-test to plan the treatment for the students, and giving the treatment by using TikTok Video. The Mean score of post-tests was 89.05 was higher than the control group with a mean score of 71.7. It meant that the result of the post-test in the experimental group was better than the control group. The result of this research is that appyling TikTok Videos to increase students’ listening comprehension was effective